A Case of Mixed Connective Tissue Disease Associated with Graves' Disease - M. Erkan Kozanoğlu,; İlke Coşkun Benlidayı,; Murat Sert, (Archives of Rheumatology, 2008)
A 23-year-old housewife admitted to hospital complained swelling, pain and skin color changes in both hands, and generalized arthralgia and myalgia. She had a butterfly malar rash, puffy hands, arthritis affecting the right second and third proximal interphalangeal and left knee joints. Anti-nuclear antibody was positive, anti-ribosomal nuclear protein antibody titer was found to be increased, C-reactive protein and erythrocyte sedimentation rate were slightly higher. Mixed connective tissue disease was diagnosed on the basis of the findings of synovitis, Raynaud's phenomenon and positive anti-ribosomal nuclear protein antibody and the patient was administered on a combination of oral prednisolone and methotrexate. After one year, a significant increase in the serum free T3 and free T4 and a suppression in thyroid stimulating hormone levels were noted. Both anti-microsomal and anti-thyroglobulin antibodies were also found to be increased. Thyroid scintigraphy with Tc-99 pertecnatat revealed a diffuse uptake pattern. The patient was diagnosed with Graves' disease and treated with anthythyroid drugs for 6 months and then radioactive iodine-131 ablation. In conclusion, here we report a case with mixed connective tissue disease associated with Graves' disease which is an uncommon data in literature. (Rheumatism 2008; 23: 100-2)